Imperfect data analysis. The demographic evolution of french speaking central Africa countries (Cameroon, CAR, Chad, Congo and Gabon). - (:unkn) unknown (My University, 2008)
This work aims to apply the demographic analysis approach on statistic data taken from five central African french speaking countries (Cameroon, Congo, Gabon, Republic of Central Africa and Tchad) in order to point out their weakness and propose ways to better data collection. The investigation on the evolution of demographic phenomena (fertility and mortality) between 1960 and 2000, beside the trends noticed, allows to notice the constraints of the data collection approach based on the transversal method preventing the comparison with the longitudinal method. In general, the objectives of data collection, without regard to sources, contain the limits of data use in the demographic analysis. The pursuit of the demography objectives, in terms of knowledge and action, implies taking into account the principles of the demographic analysis, while remedying the migrations marginalization, in the observation.
Keywords: African Research